(untitled) (Journal of Global Accounting, 2025)
This study examined the impact of audit quality on organizational survival of financial firms in Nigeria. The reason for this study was that, investors are now unable to make informed financial decisions that will have a positive impact on businesses as a whole due to the apparent lack of audit quality. The specifics objectives of the study are to evaluate the relationship between audit quality, to examine the influence of audit independence and to ascertain the effect of audit firm size all on financial performance of banking sector in Nigeria. Secondary data was used in this study and Ordinary Least Square (OLS) multiple regression was used to analyzed the data with the aid of Statav13 2024 output statistical software. The study employed an ex post factor research design because the data for the study was extracted from annual report and account of the Nigerian financial firms. A purposive sampling technique was employed to select 10 financial firms listed on the Nigerian Exchange Group as at 31st December, 2023. The study covered a time frame of five (5) years, starting from 2019 – 2023. The study found out that audit independence, and audit firms size has negative effect on the organizational survival, while audit quality has positive effect on financial performance. From our analyses and findings, the study therefore recommends that Invest should engaging reputable audit firms with proven track records of quality and independence, implement stricter guidelines to ensure audit independence and transparency across the banking sector and audit firms should provide continuous training and development programs to their staff to enhance audit quality in their work